2021
DOI: 10.1111/hsc.13657
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions in the long‐term care sector: A comparative study of migrant and native workers in Austria and Sweden

Abstract: Increased demand for long‐term care (LTC) services alongside precarious working conditions has resulted in labour shortages in the LTC sector, which has led to an increasing share of workers of migrant origin filling these jobs. Previous research on migrant care workers has also highlighted the seeming gap in working conditions relative to native workers. However, lack of disaggregated data on migrant and native care workers, alongside single‐case studies, may have concealed potential disadvantages faced by ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
(59 reference statements)
1
21
0
Order By: Relevance
“…Nevertheless, the dominance of verbal abuse observed in our study was also present in the pre-COVID era (see, for example, [19,53]). Our study findings showed a higher prevalence of abuse incidents among minority ethnic workers, perhaps explained by the lack of empowerment and deeply entrenched negative attitudes, including structural racism, towards minority workers [29,54]. As in other studies [19,21], we found significant differences in abuse experiences between care settings, with such incidents more common in residential care.…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, the dominance of verbal abuse observed in our study was also present in the pre-COVID era (see, for example, [19,53]). Our study findings showed a higher prevalence of abuse incidents among minority ethnic workers, perhaps explained by the lack of empowerment and deeply entrenched negative attitudes, including structural racism, towards minority workers [29,54]. As in other studies [19,21], we found significant differences in abuse experiences between care settings, with such incidents more common in residential care.…”
Section: Discussionsupporting
confidence: 76%
“…In large cities as Stockholm, the foreignborn staff in some units is the dominant staff category. In other parts of the world, there are similar patterns in older people care (Hurtado et al, 2012;Simmons et al, 2021).…”
Section: Of 11mentioning
confidence: 94%
“…These three groups should not be regarded as ‘migrant workers’ in the same way the term has been applied in extensive studies of care workers migrating from Eastern Europe to seek care work in Western Europe and from Latin America and other countries to the United States. For example, migrant care workers in many countries were covered in the early study by Redfoot and Houser (2005) and the recent work of Simmons, Rodrigues and Szebehely (2021) compares experiences in Austria and Sweden. Even in countries where those who migrate on a temporary basis may hope to stay, few are able to secure permanent residence rights of the kind formally provided in Australia's migration program.…”
Section: Discussionmentioning
confidence: 99%